Development of Love for Nature Scale - Sohail, Aroob; Tariq, Shahnila; Naseer, Hafiza Shamnaz; Ali, Shafqat (Pakistan Journal of Humanities and Social Sciences, 2023)
This topic was chosen to learn the behavior of people in the spring season, greenery approaches when flowers blossom and spread joy. How nature influence their behavior. Many researchers have found that spending time in nature can benefit with mental health problems such as anxiety and sadness. Without a doubt, Nature is the best medicine for curing any ailment or human behavior (mental health). Other than this, how many people agree with nurture too. In-depth interviews method was use in the study to understand behavior of people. Total 120 students interviewed from Lahore Punjab with age range 60-85. Results showed that total 32 items of love for nature scale (LNS) with four factors identified on the bases of EFA. It based on Likert scale. The internal reliability of the four factors was good that is .60 to .83. Inter-correlation of the subscales showed that all factors are inter-correlated however; aesthetic love indicated on-significant relationship with seasonal factor. LNS based on Pakistani culture so it may provide help on indigenous bases and for researchers to identify factors linked with nature and its relatedness with humans. Further studies are required to validate LNS and to investigate any other factor that may link with nature and human behavior. The Quran could utilize as guidance for those who are suffering emotional pain, and it attempts to help them attain an expressive quality of life. ‘There is no disease that Allah has created, except that He also has created its treatment’ (Sahih Al-Bukhari, book # 71, Hadith 582, narrated by Abu Huraira) (Amir, 2022).